On some sets of difference sequences of fuzzy numbers - Colak, R.; Altin, Y.; Mursaleen, M. (Springer, 2011)
In this paper we define the sequence space which is called the space of strongly -CesA ro summable sequences with modulus f. Furthermore the fuzzy Delta-statistically pre-Cauchy sequence is defined and the necessary and sufficient conditions are given for a sequence of fuzzy numbers to be fuzzy -statistically convergent. Also some relations between are given.
Keywords: Fuzzy numbers; Statistical convergence; Modulus function